The Catalyst of Change A Literature Review on the Effect of Entrepreneurial Mindset on Business Innovation - Sari, Utami Tunjung; Aditya, Ascasaputra; Artha, Bhenu (ADMAN: Journal of Contemporary Administration and Management, 2025)
In today’s volatile, uncertain, complex, and ambiguous (VUCA) environment, business innovation has shifted from being a strategic advantage to an essential condition for organizational survival. Firms that fail to innovate risk obsolescence in rapidly changing markets. This article presents a comprehensive literature review exploring the relationship between the Entrepreneurial Mindset (EM) and business innovation, drawing on empirical studies and theoretical frameworks published between 2020 and 2025. The findings consistently demonstrate that EM functions as a foundational antecedent to innovation, shaping how individuals and organizations respond to uncertainty and opportunity. Key cognitive dimensions of EM, such as risk propensity, tolerance for ambiguity, and proactive orientation, emerge as direct drivers of product innovation, process improvements, and digital transformation initiatives. These traits enable entrepreneurs and managers to identify opportunities, experiment with novel solutions, and adapt to disruptive technologies. Importantly, the review underscores that innovation operates as a mediating mechanism between EM and sustainable business performance. In other words, while mindset provides the cognitive foundation, it is the translation of entrepreneurial thinking into innovative practices that ensures long-term competitiveness. By integrating diverse perspectives, this review highlights the strategic importance of cultivating EM within organizations, positioning it as a catalyst for resilience, adaptability, and sustainable growth in the VUCA era.